Managing Human Resources for Total Quality - Douglas, Alexander (The TQM Journal Ser., 2022)
Contrary to the well-researched operations side of the total quality management (TQM), its human dimension TQM-based human resource management practices (HRMtqm) has started attracting attention of the scholars and practitioners only recently (Kumar et al., 2020). The critique is that compared to the intangible or the soft side, the TQM literature is heavily inclined toward the technical or hard side (Para-González et al., 2016). This interest of scholars in exploring the relationship between TQM and HRM recently is primarily driven by the latest findings that the human-related quality management creates a learning orientation and integrates knowledge to benefit the organizations (Gutierrez-Gutierrez et al., 2018). Thus, as we describe in the subsequent sections, the main objective of this special issue is to explore and examine the HRMtqm.